2014
DOI: 10.1371/journal.pone.0103159
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Early-Onset Colorectal Cancer Is a Specific Sub-Type of Cancer: A Morphological, Molecular and Genetics Study

Abstract: Sporadic early onset colorectal carcinoma (EOCRC) which has by definition no identified hereditary predisposition is a growing problem that remains poorly understood. Molecular analysis could improve identification of distinct sub-types of colorectal cancers (CRC) with therapeutic implications and thus can help establish that sporadic EOCRC is a distinct entity. From 954 patients resected for CRC at our institution, 98 patients were selected. Patients aged 45–60 years were excluded to help define “young” and “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 43 publications
6
105
2
Order By: Relevance
“…In recent years, we have encountered several BRAF -mutated CRCs in patients aged under 30 years, suggesting that this might be a common genetic change in EOCRC. However, the findings of studies in Western countries are in disagreement with our observation 8 9 18. Therefore, in this study, we analysed the molecular characteristics of EOCRC in Taiwan.…”
Section: Introductioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In recent years, we have encountered several BRAF -mutated CRCs in patients aged under 30 years, suggesting that this might be a common genetic change in EOCRC. However, the findings of studies in Western countries are in disagreement with our observation 8 9 18. Therefore, in this study, we analysed the molecular characteristics of EOCRC in Taiwan.…”
Section: Introductioncontrasting
confidence: 81%
“…BRAF mutation rates in EOCRCs are lower than, or comparable with, those in older patients in two studies from the USA and one from France 8 9 18. Notably, in the studies of Chang et al and Kirzin et al , no BRAF mutation was detected in EOCRCs even though only microsatellite stable (MSS) tumours were considered 9 18. As early-onset MSI-H tumours are often associated with HNPCC and unlikely to have a BRAF mutation, exclusion of MSI-H tumours would probably increase the BRAF mutation rate.…”
Section: Discussionmentioning
confidence: 94%
“…SSA/P, being located in the proximal colon in young adults, are therefore unlikely to be the precursor lesion for most early-onset CRC. In support of this premise, somatic BRAF mutation, the molecular genetic hallmark of SSA/P, is relatively rare in CRC from young adults, being present at (3/45) 7% in a Norwegian study [16], 1/68 (2%) in a Spanish report [8], and in 0/39 (0%) from France [14]. Activating mutations in BRAF are present in 14–16% of all population-based CRC [28, 29].…”
Section: Discussionmentioning
confidence: 98%
“…FAP cases are observed in less than 1% frequency in total CRC cases. Thus, 70% of all CRC and the majority of EOCRC cases are introduced in sporadic form [136][137][138] . Sporadic EOCRCs are classified into two major groups.…”
Section: Sporadic Forms Of Eocrcmentioning
confidence: 99%
“…Both genetic and epigenetic inactivation of MMR genes result in a mutator phenotype, mutations in cancer related genes and CRC development [144] . Kirzin et al [137] identified CTNNB1 as one of the most over-expressed genes in MSS-young patients compared to MSS-old patients and this leads to an over-activation of beta catenin in sporadic EOCRC. In addition, FernandezRozadilla et al [145] determined a heterozygous deletion in the 10q22-q23 region involving BMPR1A gene of EOCRC cases with MMR proficiency.…”
Section: Sporadic Forms Of Eocrcmentioning
confidence: 99%